Effect of light-dark cycles on hydrogen and poly-β-hydroxybutyrate production by a photoheterotrophic culture and Rhodobacter capsulatus using a dark fermentation effluent as substrate. (February 2017) - Montiel Corona, Virginia; Le Borgne, Sylvie; Revah, Sergio; Morales, Marcia
Graphical abstract: Highlights: Photoperiods might offer energy savings in H2 production by photofermentation. IZT culture kept H2 production under both continuous lighting and photoperiods. H2 production by R. capsulatus declined under photoperiods. R. capsulatus tripled and IZT doubled PHB accumulation under photoperiods. Abstract: A Rhodobacter capsulatus strain and a photoheterotrophic culture (IZT) were cultivated to produce hydrogen under different light-dark cycles. A dark fermentation effluent (DFE) was used as substrate. It was found that IZT culture had an average cumulative hydrogen production (Paccum H2 ) of 1300 ± 43 mL H2  L −1 under continuous illumination and light-dark cycles of 30 or 60 min. In contrast, R. capsulatus reduced its Paccum H2 by 20% under 30:30 min light-dark cycles, but tripled its poly-β-hydroxybutyrate (PHB) content (308 ± 2 mgPHB gdw −1 ) compared to continuous illumination. The highest PHB content by IZT culture was 178 ± 10 mgPHB gdw −1 under 15:15 min light-dark cycles. PCR-DGGE analysis revealed that the IZT culture was mainly composed of Rhodopseudomonas palustris identified with high nucleotide similarity (99%). The evaluated cultures might be used for hydrogen and PHB production. They might provide energy savings by using light-dark cycles and DFE valorization.